Safety of titanium dioxide (E171) as a food additive for humans - Warheit, David B. (Frontiers in Toxicology, 2024)
Titanium dioxide (TiO2), also known as E171, is commonly used as a white colorant in food, pharmaceuticals, cosmetics, and toothpaste. However, in May 2021, the European Food Safety Authority (EFSA) expert panel, in evaluating the safety of titanium dioxide (E171) as a food additive, concluded that a concern for genotoxicity could not be ruled out. This occurred several years after EFSA had previously considered titanium dioxide to be safe as a food additive. EFSA based this new interpretation on the results of genotoxicity tests of TiO2 nanomaterials. EFSA noted that available data are insufficient to define threshold doses/concentrations of TiO2 particles below which genotoxicity will not occur in tissues containing these particles. Here, it is argued that EFSA made a manifest error regarding the safety of titanium dioxide (E171) particles as a food additive for humans. First, the notion of particle size distribution of TiO2 particles is explained. Second, the changing opinions from the various EFSA evaluations in 2016, 2018, 2019 vs. 2021 are discussed. Third, the low toxicity of TiO2 particles is described in rats exposed by oral gavage and feeding studies in rats and mice. Fourth, the importance of low absorption rates from the gastrointestinal tract vs. circulation in rats and humans but not in mice is identified. Fifth, other international health scientists have weighed in on the EFSA (EFSA J, 2021, 19 (5), 6585) decision and generally disagreed with EFSA’s opinion on the safety of E171 TiO2. A common theme voiced by the United Kingdom, Canada, Australia, and New Zealand agencies is that it is inappropriate to compare nanoparticle toxicity studies of dispersed/sonicated nanoparticles with the content of E171 TiO2 in foods because the test materials used in key studies considered by EFSA (EFSA J, 2021, 19 (5), 6585) are not representative of E171 TiO2 particles. Finally, a group of experts recently considered the genotoxicity of TiO2 and could not find support for a direct DNA damaging mechanism of TiO2 (nano and other forms). For these reasons, it is suggested that EFSA made a manifest error on the safety of E171 as a food additive.